The impact of tube current and iterative reconstruction algorithm on dose and image quality of infant CT head examination - Muhammad, N.A.; Karim, M.K.A.; Harun, H.H.; Rahman, M.A.A.; Azlan, R.N.R.M.; Sumardi, N.F. (Elsevier, 2022)
Computed Tomography (CT) scan examination has been recognized for its potential in contributing high radiation doses, which raised a public concern towards pediatric exposure, especially infants. Thus, the optimization is vital through well-balanced levels of radiation and image quality. Hence, this study aimed to investigate optimized CT acquisition parameter on radiosensitive organs of infant CT head examination and its influence on the image quality. This study utilized a 1-year-old anthropomorphic phantom and thermoluminescence dosimeter (TLD) for organ dose assessment. The examination was performed by using 128 multi-slice CT (Ingenuity Core, Philips, Netherlands) and varying the tube current and iterative reconstruction algorithm (iDose4) levels. During the process, the reference mAs (ref. mAs) were altered while maintaining the tube potential at 100 kVp. Five protocols were established and denoted by P1, P2, P3, P4, and P5. As per measurement, 3 calibrated TLD chips were implanted into the phantom on slab numbers 2, 4, and 7 that represented brain, lens, and thyroid, respectively. Image quality was evaluated by utilizing the objective assessment in terms of signal to noise ratio (SNR) and contrast to noise ratio (CNR) and subjective image quality using the Visual Grading Analysis (VGA) technique in terms of sharpness, noise, and artefact were assessed from each protocol. Notably, the dose was decreased up to 30% along with the reduction of tube current and the improvement of SNR and CNR values for parameters that enable the iterative reconstruction algorithm. Hence, optimization of CT acquisition parameter should be evaluated and monitored accordingly.